Optical properties of monolayer tinene in electric fields - Rong-Bin Chen (Nature Portfolio, 2017)
Abstract The absorption spectra of monolayer tinene in perpendicular electric fields are studied by the tight-binding model. There are three kinds of special structures, namely shoulders, logarithmical symmetric peaks and asymmetric peaks in the square-root form, corresponding to the optical excitations of the extreme points, saddle points and constant-energy loops. With the increasing field strength, two splitting shoulder structures, which are dominated by the parabolic bands of 5p z orbitals, come to exist because of the spin-split energy bands. The frequency of threshold shoulder declines to zero and then linearly grows. The third shoulder at 0.75~0.85 eV mainly comes from (5p x , 5p y ) orbitals. The former and the latter orbitals, respectively, create the saddle-point symmetric peaks near the M point, while they hybridize with one another to generate the loop-related asymmetric peaks. Tinene quite differs from graphene, silicene, and germanene. The special relationship among the multi-orbital chemical bondings, spin-orbital couplings and Coulomb potentials accounts for the feature-rich optical properties.